Neutronic Activation of Amazon Technogenic Deposit Soil Used as Raw Material in Brick Manufacture - Passos de Oliveira, Antonio Carlos Santos do Nascimento; Macêdo, Alcebíades Negrão; Souza, José Antonio da Silva; Oliveira, Dênio Ramam Carvalho (Anuário do Instituto de Geociências, 2024)
Considering the extraction of soil from Technogenic Deposits, may result in the risk, this article investigated whether in the brick making process, there is a possibility that chemical elements, considered linked to human illness, may have evidence of release to the environment. The adopted strategy was to subject both the soil, as well as the brick manufactured with this soil, to the Neutronic Activation test, later, through the mass balance, to verify the variations in the global concentrations of chemical elements. The results show that of the 27 elements analyzed, 25 showed a reduction in their concentrations after the burning of the soil. As the systematic literature review points out, the release of these chemical elements to the environment, is intrinsically linked to the decrease in the environmental quality of the built environment, therefore, it is an indication of possible risks for human health.